Pengaruh Beban Kerja Terhadap Stres Kerja Pada Karyawan di PT Bank Central Asia TBK Kantor Cabang Utama Depok - Ahmat Setiabudi; Rimah Nurjanah (Peneliti.net, 2022)
The purpose of this research is to find out about how workloads affect the work stress. Population of this research is employees on head branch of the PT Bank Central Asia Inc, as much as 58 employees. The sampling technique used in this research is the Incidental Sampling technique with a sample of 51 respondents obtained from the calculation of the slovin formula. The data analysis method used is a simple linear regression test. The result on the normality test with one-sampleKolmogorov-Smirnov test method obtained the Asymp. Sig (2-tailed test) is at value of 0.200. Hence, it can be said that the data distribution result that has been acquired is distributed normally. The value of the simple linear analysis regression on the sig regression value is at 0.000. If observed by the basic of decision making 0,000 < 0,05 means that the X variable, also known as, the workload, affects the Y variable or also known as the work stress. The result of determination coefficient (R2) has found that the value of R Square is at 0.550. Therefore, it can be summarized that the value of the impacted variable “workload” against the variable “work stress” is at 55%. The summary of this research is to imply that the more workload that is received, the bigger their work stress that is felt by the employees on Head Branch of PT. Bank Central Asia Tbk in Depok.